Assessment of Solubility and Sorption of Cention-N, Zirconomer, and Conventional GIC Restorative Materials Immersed in Different Beverages - Sanjit Kumar Sahoo; Naveen R. Reddy; Vaibhav Awinashe; Shahzad A. Shah; Swetha Vempalli; Noura Alessa; Prajwal Shetty; Vardarajula V. Ramaiah (Journal of Pharmacy and Bioallied Sciences)
Objectives: The objective of this research was to assess the solubility and sorption values of various restorative materials immersed in different beverages. Materials and Method: Thirty circular discs per restorative material were prepared with 10 in each group; Group I-cention-N, Group II-Zirconomer, and Group III-glass-ionomer cements. Ten specimens of each material were immersed in the test media (various beverages such as tea, coffee, and orange juice) for six days. Water sorption and solubility were calculated using ISO guidelines. Result: There was statistically considerable variation between the three tested materials. Amongst the beverages tested orange juice persuaded both sorption and solubility values more than the other media. Conclusion: Conventional GIC was found to have more sorption and solubility values than the other two materials.